An updated meta-analysis of the signal transducer and activator of transcription 4 (STAT4) rs7574865 G/T polymorphism and rheumatoid arthritis risk in an Asian population. (November 2014) - Jiang, X; Zhou, Z; Zhang, Y; Yang, H; Ren, K
<x xml:space="preserve">Abstract</x> Objectives: Signal transducer and activator of transcription 4 (STAT4) transmits signals induced by the cytokines interleukin (IL)-12, IL-23, and interferon (IFN)-γ, which play an important role in the development of rheumatoid arthritis (RA). Studies have shown conflicting results concerning the association between the rs7574865 G/T polymorphism in the STAT4 gene and RA in an Asian population. We have performed a meta-analysis to examine this relationship. Method: We searched PubMed and WanFang databases for all papers published up to 5 October 2013. Eight case–control studies with 6029 cases and 4685 controls were retrieved based on the search criteria for RA susceptibility related to the STAT4 rs7574865 G/T polymorphism. Risk ratios (RRs) and 95% confidence intervals (CIs) were used to assess the strength of this association. Publication bias was assessed using Begg's test. Results: A significant association was found between the STAT4 rs7574865 G/T polymorphism and RA risk (e.g. GG+GT vs. TT: RR 0.96, 95% CI 0.95–0.97; GG+TT vs. GT: RR 0.94, 95% CI 0.91–0.97). Subgroup analysis of rheumatoid factor (RF) status revealed a protective relationship between the STAT4 rs7574865 G/T polymorphism and RF+/RF− RA risk. A similar relationship was detected in the anti-cyclic citrullinated peptide (CCP) status subgroup. No clear evidence of publication bias was detected in the overall analysis. Conclusions: Our study indicates that the STAT4 rs7574865 G/T polymorphism was significantly associated with a decreased RA risk in an Asian population.